Evidence for posttranscriptional regulation of the keratins expressed during hyperproliferation and malignant transformation in human epidermis (The Rockefeller University Press, 1986)
Keratin K6 is a protein that is expressed in human skin under conditions of hyperproliferation (e.g., wound-healing, psoriasis, and cell culture) and malignant transformation (e.g., squamous cell carcinomas). When induced, the appearance of K6 is rapid: if skin tissue is placed in radiolabeled culture medium, this protein can be detected within an hour. The regulation of K6 seems to be controlled partly by a posttranscriptional mechanism: At least two K6 genes are actively transcribed both in vivo, when the protein is not made, as well as in vitro, when abundant levels of the protein are expressed. Substantial levels of K6a and K6b RNAs can be detected in skin by Northern Blot analysis, and these RNAs are largely, if not fully translatable in vitro. In situ hybridizations reveal that the RNAs are distributed throughout the living layers of the epidermis. The rapid induction of K6 expression through a posttranscriptional regulatory mechanism suggests that this keratin may play an important role in designing a cytoskeletal architecture that is compatible with the hyperproliferative state.